Positive electrode material and its manufacturing method
A high nickel positive electrode material with a lithium iron phosphate coating layer addresses low rate performance and cost issues by improving power density and rate characteristics through mechanical mixing, ensuring efficient charge/discharge performance and reduced costs.
Patent Information
- Application Number
- JP2023076932
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-01
- Filing Date
- 2023-05-08
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-05-08
AI Technical Summary
High nickel positive electrode materials exhibit low rate performance, making them unsuitable for devices requiring high discharge rates, and their production is hindered by fluctuating cobalt prices, necessitating a cost-effective solution with improved power density and rate characteristics.
A high nickel positive electrode material with a coating layer composed of lithium iron phosphate or heterosite iron phosphate, combined with a carbon coating, is manufactured using a mechanical mixing method to enhance rate characteristics and prevent electrolyte penetration, ensuring low impedance and good charge/discharge performance.
The solution significantly improves the rate characteristics and maintains low manufacturing costs by adding a small amount of iron phosphate compound, enhancing electronic conductivity and preventing structural defects, resulting in improved charge/discharge performance.
Smart Images

Figure 0007621415000004 
Figure 0007621415000005 
Figure 0007621415000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode material for a secondary battery, and more particularly to a high-nickel positive electrode material with a coating layer that can reduce costs while improving high power density and rate characteristics, and a method for producing the same. [Background technology]
[0002] In recent years, the performance requirements for electric vehicles and power storage devices have been increasing, and the secondary batteries used in them are also required to have high performance. Among the various types of batteries, lithium-ion batteries using ternary positive electrode materials such as nickel-cobalt-manganese (NCM) are currently mainstream due to their high capacity.
[0003] Since the power density of the battery is directly proportional to the nickel content in the positive electrode material and the price of cobalt metal fluctuates drastically, the current mainstream development policy is to increase the nickel content in the positive electrode material so as to reduce costs while improving the power density. However, the high-nickel positive electrode material itself has a problem of low rate performance, and it is difficult for a lithium-ion battery made of this material to be applied to a device that requires a high discharge rate.
[0004] The present invention has been made in view of the above circumstances, and in order to solve the shortcomings of the conventional technology, provides a high-nickel positive electrode material having a coating layer, which can reduce costs while improving high power density and rate characteristics, and a method for producing the same. Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a positive electrode material and a method for producing the same. The positive electrode material includes a core layer and a coating layer that coats the core layer. The core layer has a composition of Li[Ni x Co y Mn zIt is composed of a ternary material that is O2, where x + y + z = 1, 0.8 < x < 1, 0 < y < 0.2, and 0 < z < 0.2. Due to the high nickel content in the core layer, a cathode material with high output density and low cost can be realized. The coating layer is composed of, for example, lithium iron phosphate (LiFePO4, LFP) material or heterosite iron phosphate (H-FP) material, and is formed by the aggregation of a plurality of particles. Since the lithium iron phosphate material and the heterosite iron phosphate material themselves have good rate characteristics, the coating layer composed of them can further improve the rate characteristics of the cathode material. Also, the weight ratio of the coating layer in the cathode material is, for example, 0.2 wt% - 5 wt%. By adding only a small amount of iron phosphate compound material, a coating layer that improves the rate characteristics of the cathode material can be formed, so the manufacturing cost can be further reduced. Each coating layer particle of the cathode material is coated with a carbon coating layer, which can enhance the electron conductivity between the coating layer particles and improve the performance of the cathode material.
[0006] Another object of the present invention is to provide a cathode material and a method for manufacturing the same. For example, by mixing a ternary material with a high nickel content and an iron phosphate compound material by a mechanical mixing method, which is one of the Mechanofusion methods, a high nickel cathode material with a coating layer can be obtained. The operating temperature during the mixing process is, for example, 25 °C - 45 °C, the time is 5 minutes - 25 minutes, and the range of the rotation speed is, for example, 1000 rpm - 3000 rpm. By controlling the mixing method, operating temperature, rotation speed, and time of the ternary material and the iron phosphate compound material, structural defects of the coating layer caused by high temperature and excessive friction between particles can be prevented, and by forming a dense coating layer, it is possible to avoid the electrolyte from easily penetrating into the interior of the cathode material, and ensure low impedance and good charge-discharge performance of the cathode material.
Means for Solving the Problems
[0007] In order to achieve the above object, the present invention provides a positive electrode material comprising a core layer and a coating layer that coats the core layer. The core layer is composed of a ternary material, and the composition of the ternary material is Li[Ni x Co y Mn z O2, where x + y + z = 1, 0.8 < x < 1, 0 < y < 0.2, and 0 < z < 0.2. The coating layer is composed of an iron phosphate compound material, and the coating layer is formed by aggregation of a plurality of first particles. Preferably, the particle size of the core layer is 4 μm to 15 μm. Preferably, the iron phosphate compound material is composed of any one of lithium iron phosphate (LiFePO4) and heterosite iron phosphate (Heterosite FePO4). Preferably, the particle size of the first particles is 0.1 μm to 3 μm. Preferably, the positive electrode material is provided with a carbon coating layer that coats the first particles, and the thickness of the carbon coating layer is 3 nm to 10 nm. Preferably, the weight ratio of the core layer in the positive electrode material is 95 wt% to 99.8 wt%. Preferably, the weight ratio of the coating layer in the positive electrode material is 0.2 wt% to 5 wt%. Preferably, the weight ratio of the coating layer in the positive electrode material is 0.2 wt% to 3 wt%.
[0008] In order to achieve the above object, the present invention provides a ternary material having a composition of Li[Ni x Co y Mn z O2, where x + y + z = 1, 0.8 < x < 1, 0 < y < 0.2, and 0 < z < 0.2, and provides an iron phosphate compound material, and mixes the ternary material and the iron phosphate compound material by a mechanical mixing method to obtain a positive electrode material. Step (b) is a method for manufacturing a positive electrode material, which includes step (a) and step (b) in which the positive electrode material includes a core layer and a coating layer, the core layer is composed of a ternary material, the coating layer coats the core layer, the coating layer is composed of an iron phosphate compound material, and the coating layer is formed by aggregation of a plurality of first particles. Preferably, the particle size of the core layer is 4 μm to 15 μm. Preferably, the iron phosphate compound material is comprised of any one of lithium iron phosphate (LiFePO4) and heterosite iron phosphate (Heterosite FePO4). Preferably, the particle diameter of the first particles is 0.1 μm to 3 μm. Preferably, the positive electrode material includes a carbon coating layer that coats the first particles, and the carbon coating layer has a thickness of 3 nm to 10 nm. Preferably, the weight ratio of the core layer in the positive electrode material is 95 wt % to 99.8 wt %. Preferably, the weight ratio of the coating layer in the positive electrode material is 0.2 wt % to 5 wt %. Preferably, the weight ratio of the coating layer in the positive electrode material is 0.2 wt % to 3 wt %. Preferably, the mechanical mixing method includes a mechanical blending process. Preferably, the time for mixing the ternary material and the iron phosphate compound material by mechanical mixing is 5 to 25 minutes. Preferably, the rotation speed of the mechanical mixing method is in the range of 1000 rpm to 3000 rpm. Preferably, the operating temperature of the mechanical mixing method is 25°C to 45°C. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a conceptual structural diagram of a positive electrode material according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a flowchart of a method for producing a positive electrode material according to an embodiment of the present invention. [Figure 3A] 1 is an SEM image of a positive electrode material of a comparative example. [Figure 3B] 1 is an SEM image of a positive electrode material of a comparative example. [Figure 4A] 1 is a SEM image of a positive electrode material according to a first embodiment of the present invention. [Figure 4B] 1 is a SEM image of a positive electrode material according to a first embodiment of the present invention. [Figure 5A] 1 is an SEM image of a positive electrode material of a comparative example. [Figure 5B]1 is a SEM image of a positive electrode material according to a second embodiment of the present invention. [Figure 6A] 1 is an SEM image of a positive electrode material of a comparative example. [Figure 6B] 1 is a SEM image of a positive electrode material according to a third embodiment of the present invention. [Figure 7A] 1 is an SEM image of a positive electrode material of a comparative example. [Figure 7B] 13 is an SEM image of a positive electrode material according to a fourth embodiment of the present invention. [Figure 8A] FIG. 11 is a potential-capacity charging curve diagram of a comparative example and first, second, third and fourth examples of the present invention. [Figure 8B] FIG. 11 is a potential-capacity discharge curve diagram of a comparative example and first, second, third and fourth examples of the present invention. [Figure 9A] 4 shows electrochemical impedance spectra of a comparative example, a first embodiment of the present invention, and a second embodiment of the present invention. [Figure 9B] 11 shows electrochemical impedance spectra of the third and fourth embodiments of the present invention. [Figure 10A] FIG. 4 is a charging curve diagram showing the relationship between the capacity retention rate and the number of cycles for a comparative example, and the first and second examples of the present invention. [Figure 10B] FIG. 13 is a graph showing discharge curves of the capacity retention rate versus the number of cycles for a comparative example, and the first and second examples of the present invention. [Figure 11] FIG. 2 is a capacity-cycle discharge curve diagram of a comparative example, a first embodiment and a second embodiment of the present invention at different charge and discharge rates. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Some exemplary embodiments embodying the features and advantages of the present invention will be described in detail in the following. The present invention can be modified in various ways without departing from the scope of the present invention, and the following description and drawings are used to describe the present invention and are not intended to limit the present invention. In addition, in the detailed description of the present invention, the arrangement of a first feature on or above a second feature includes an embodiment in which the arranged first feature and the second feature are directly connected to each other, and an embodiment in which the first feature and the second feature are not directly connected to each other via another structure between the first feature and the second feature. In addition, the terms "first", "second", "third", etc. are used to describe different configurations described in the claims, and these configurations are not limited to these terms, and in the content related to the embodiments, although the corresponding configurations are represented by different symbols, the first configuration can be represented as the second configuration, and the second configuration can be represented as the first configuration, without departing from the embodiments of the present invention. In addition, the term "and / or" means one and a plurality of related elements or all combinations thereof. The term "about" refers to an average value within an acceptable standard error range recognized by a person skilled in the art. Unless expressly defined in the embodiments relating to operation / operation, all numerical ranges, amounts, values, percentages, etc. described herein (e.g., angles, durations, temperatures, operating conditions, ratios and corresponding percentages, etc.) should be understood in all embodiments by the terms "about" or "substantially". In addition, unless otherwise stated in the content, all numerical values in the present invention and claims can be taken as approximations that can be varied as necessary. For example, each parameter may be interpreted in light of at least the number of significant digits described, applying ordinary rounding rules. In addition, numerical ranges herein can be expressed as ranges from one endpoint to the other endpoint or between two endpoints. It should be noted that all ranges described herein include the endpoints unless otherwise defined.
[0011] Figure 1 is a structural conceptual diagram of a positive electrode material according to an embodiment of the present invention. In this embodiment, the positive electrode material 1 includes a core layer 10 and a coating layer 20 that covers the core layer 10. The core layer 10 is composed of a ternary material, and the composition of the ternary material is Li[Ni x Co y Mn z O2, where x + y + z = 1, 0.8 < x < 1, 0 < y < 0.2, and 0 < z < 0.2. The coating layer 20 is composed of an iron phosphate compound material and is formed by aggregation of a plurality of first particles 21. In this embodiment, the ternary material is, for example, a nickel-cobalt-lithium-manganese-oxide (NCM) material with a composition of Li[Ni x Co y Mn z O2, where x = 0.83, y = 0.12, and z = 0.05, that is, the ratio of nickel, cobalt, and manganese in the nickel-cobalt-lithium-manganese-oxide material is 83:12:5. Preferably, the nickel-cobalt-lithium-manganese-oxide material is synthesized by, for example, a solid-state synthesis method, the median diameter (D50) ranges from 9 μm to 13 μm, the specific surface area is 1 m 2 / g or less, and the tap density is 2.5 g / ml to 3 g / ml. In another embodiment, the ternary material may be, for example, a nickel-cobalt-lithium-manganese-oxide (NCM) material with a composition ratio different from the above-described composition ratio and is produced by a sol-gel process. Note that the type, composition ratio, material characteristics, and manufacturing process of the ternary material of the present invention are not limited, and details are omitted here. Since the nickel content in the core layer 10 is high, a positive electrode material 1 with high output density and low cost can be obtained.
[0012] In this embodiment, the iron phosphate compound material is composed of either lithium iron phosphate (LiFePO4) or heterosite iron phosphate (Heterosite FePO4). In this embodiment, the lithium iron phosphate material is synthesized by, for example, solid-state synthesis, and the heterosite iron phosphate is synthesized by, for example, liquid-phase reaction, but the present invention is not limited thereto. Since the lithium iron phosphate material and the heterosite iron phosphate material have good rate characteristics themselves, the rate characteristics of the positive electrode material 1 can be further improved by the coating layer 20 composed of them. In this embodiment, the positive electrode material 1 further includes, for example, a carbon coating layer 30, which coats the first particles 21 and has a thickness of 3 nm to 10 nm. This can increase the electronic conductivity of the coating layer and improve the performance of the positive electrode material. In this embodiment, the carbon coating layer 30 of the positive electrode material 1 is composed of, for example, a carbon coating layer in the iron phosphate compound material treated by carbon coating treatment. The carbon coating treatment of the iron phosphate compound material can be achieved by, for example, mechanical mixing, spray drying, heat treatment, etc. This is not an essential technical feature of the present invention, so details are omitted here.
[0013] In this embodiment, the particle diameter of the core layer 10 is 4 μm to 15 μm. The particle diameter of the first particles 21 is 0.1 μm to 3 μm. In this embodiment, the particle diameters of the core layer 10 and the first particles 21 are detected by, for example, a scanning electron microscope (SEM). Note that the particle diameters of the core layer 10 and the first particles 21 may be detected by a transmission electron microscope (TEM) or other equipment capable of surface analysis, and the present invention is not limited thereto.
[0014] In this embodiment, the weight ratio of the core layer 10 in the positive electrode material 1 is 95 wt% to 99.8 wt%. The weight ratio of the coating layer 20 in the positive electrode material 1 is 0.2 wt% to 5 wt%. In another embodiment, the weight ratio of the coating layer 20 in the positive electrode material 1 is, for example, 0.2 wt% to 3 wt%, preferably 0.2 wt% to 1 wt%. In this embodiment, the weight ratio of the coating layer 20 in the positive electrode material 1 is, for example, 0.3 wt%. Thus, by simply adding a small amount of iron phosphate compound material to the positive electrode material 1 of the present invention, a coating layer 20 that can improve the rate characteristics of the positive electrode material can be formed, and the manufacturing cost can be further reduced.
[0015] According to the positive electrode material 1 described above, the present invention further provides a method for manufacturing the positive electrode material 1. FIG. 2 is a flowchart of a method for manufacturing a positive electrode material according to an embodiment of the present invention. First, as shown in step S1, a ternary material having a composition of Li[Ni x Co y Mn z O2 is provided, where x + y + z = 1, 0.8 < x < 1, 0 < y < 0.2, and 0 < z < 0.2. In this embodiment, the ternary material is, for example, a nickel-cobalt-lithium-manganese-oxide (NCM) material having a composition of Li[Ni x Co y Mn z O2, and x = 0.83, y = 0.12, z = 0.05, that is, the ratio of nickel, cobalt, and manganese in the nickel-cobalt-lithium-manganese-oxide material is 83:12:5. Preferably, the nickel-cobalt-lithium-manganese-oxide material is synthesized, for example, by a solid-state synthesis method, has a median diameter (D50) of 9 μm to 13 μm, and a specific surface area of 1 m 2 / g or less, and the tap density is 2.5 g / ml to 3 g / ml. In another embodiment, the ternary material is, for example, a nickel-cobalt-lithium-manganese-oxide (NCM) material having a composition ratio different from the above-mentioned composition ratio, and may be synthesized by a sol-gel process. The type, composition ratio, material properties, and manufacturing process of the ternary material of the present invention are not limited, and details are omitted here. Since the nickel content in the core layer 10 is high, a positive electrode material 1 with high power density and low cost can be obtained.
[0016] As shown in step S2, an iron phosphate compound material is prepared, and the ternary material and the iron phosphate compound material are mechanically mixed to obtain a positive electrode material 1. The positive electrode material 1 includes a core layer 10 and a coating layer 20 covering the core layer 10, and the core layer 10 is composed of a ternary material. The coating layer 20 is composed of an iron phosphate compound material and is formed by agglomeration of a plurality of first particles 21. In this embodiment, the mechanical mixing method includes, for example, a mechanical fusion method. The operating temperature of the mechanical method is, for example, 25°C to 45°C, the rotation speed range is 1000 rpm to 3000 rpm, and the mixing time of the ternary material and the iron phosphate compound material is, for example, 5 minutes to 25 minutes. In this embodiment, the rotation speed of the mechanical mixing method is, for example, 2000 rpm, and the mixing time of the ternary material and the iron phosphate compound material is set to, for example, 15 minutes, but the present invention is not limited thereto. By controlling the mixing method, operating temperature, rotation speed and time of the ternary material and the iron phosphate compound material, it is possible to prevent structural defects in the coating layer 20 caused by high temperature or excessive friction between particles, and to avoid the formation of an excessively dense coating layer 20 that makes it difficult for the electrolyte to penetrate into the positive electrode material 1, thereby ensuring low impedance and good charge and discharge performance of the positive electrode material 1.
[0017] The manufacturing process and effects of the present invention will be described in detail below with reference to comparative examples and examples.
[0018] Comparative Example: The comparative example is a positive electrode material made of a ternary material. The composition of the comparative ternary material is Li[Ni x Coy Mn z ]O2, where x = 0.826, y = 0.124, and z = 0.05, that is, the ratio of nickel, cobalt, and manganese in the nickel-cobalt-lithium-manganese-oxide material is 82.6:12.4:5. The median diameter (D50) of the ternary material of the comparative example is 9.85 μm, and the specific surface area is 0.27 m 2 / g and tap density is 2.94 g / ml.
[0019] First Example: The first embodiment is a cathode material manufactured as follows. First, a ternary material is provided (prepared). The ternary material of the first embodiment has the composition Li[Ni x Co y Mn z ]O2, and has the same composition ratio and material properties as the ternary material of the comparative example, so details are omitted here.
[0020] Then, the ternary material and the iron phosphate compound material are mixed by mechanical mixing to obtain a positive electrode material. The iron phosphate compound material in the first embodiment is heterosite iron phosphate (Heterosite FePO4, H-FP), and the molar ratio of the added ternary material to the iron phosphate compound material is 1:0.03. The mechanical mixing method in the first embodiment is a mechanical fusion method, in which the operating temperature is 25°C to 45°C, the rotation speed range is 2000 rpm, and the mixing time is 15 minutes. During the mixing process, the operating temperature is cooled by water cooling.
[0021] The method for producing the heterosite iron phosphate is as follows. First, lithium iron phosphate and water are uniformly stirred, and peracetic acid (PAA) is gradually added at a constant flow rate to form a mixture. Next, the mixture is left to stand for a certain period of time, filtered, and dried by heating in an inert gas atmosphere to obtain the heterosite iron phosphate of the first embodiment.
[0022] Example 2: The manufacturing method of the second embodiment is almost the same as that of the first embodiment, but the iron phosphate compound material of the second embodiment is lithium iron phosphate (LiFePO4, LFP), and the mixing time is 15 minutes.
[0023] Example 3: The manufacturing method of the third embodiment is almost the same as that of the first embodiment, but the iron phosphate compound material of the third embodiment is heterosite iron phosphate (Heterosite FePO4, H-FP), and the mixing time is 30 minutes. The manufacturing method of the heterosite iron phosphate of the third embodiment is similar to that of the heterosite iron phosphate of the first embodiment.
[0024] Example 4: The manufacturing method of the fourth embodiment is almost the same as that of the second embodiment, but the iron phosphate compound material of the fourth embodiment is lithium iron phosphate (LiFePO4, LFP), and the mixing time is 30 minutes.
[0025] 3A-3B are SEM images of the positive electrode material of the comparative example. FIG. 4A-4B are SEM images of the positive electrode material of the first embodiment of the present invention. FIG. 5A-5B are SEM images of the positive electrode material of the second embodiment of the present invention. FIG. 6A-6B are SEM images of the positive electrode material of the third embodiment of the present invention. FIG. 7A-7B are SEM images of the positive electrode material of the fourth embodiment of the present invention. As shown in FIG. 4A-7B, the particle diameter of the core layer 10 of the embodiment of the present invention is 4 μm-15 μm, and the particle diameter of the first particle 21 is 0.1 μm-3 μm. At the same time, the structure of the coating layer 20 of the third and fourth embodiments, in which the mixing time is 30 minutes, is relatively dense, compared with the first and second embodiments, in which the mixing time is 15 minutes. Thus, by controlling the mixing time of the ternary material and the iron phosphate compound material, it is possible to avoid the formation of an overly dense coating layer 20 that would make it difficult for the electrolyte to penetrate into the positive electrode material 1, and further to ensure low impedance and good charge / discharge performance of the positive electrode material 1.
[0026] FIG. 8A is a potential-capacity charging curve diagram of the comparative example, the first embodiment, the second embodiment, the third embodiment, and the fourth embodiment of the present invention. FIG. 8B is a potential-capacity discharging curve diagram of the comparative example, the first embodiment, the second embodiment, the third embodiment, and the fourth embodiment of the present invention. FIG. 8A and FIG. 8B are the results of measurement at a 0.1C charge-discharge rate (C-rate) of button batteries constructed from the comparative example, the first embodiment, the second embodiment, the third embodiment, and the fourth embodiment of the present invention, respectively. The positive electrode sheet of the button battery is constructed with a ratio of positive electrode material, conductive assistant, and adhesive of 90:5:5, the negative electrode is lithium metal, and the separator is Celgard 2320. The electrolyte of the button battery contains 1.2 M lithium hexafluorophosphate (LiPF6), ethylene carbonate (EC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC) and 2 wt% fluoroethylene carbonate (FEC). Table 1 shows the measurement results. As shown in Fig. 8A, Fig. 8B and Table 1, the charge-discharge performance of the first and second examples with a mixing time of 15 minutes is not significantly different from that of the comparative example, but the third and fourth examples with a mixing time of 30 minutes show a relatively low discharge voltage plateau voltage, a slow decrease in voltage over a long period of time, and a first cycle discharge capacity compared to the comparative example. As a result, by controlling the mixing time of the ternary material and the iron phosphate compound material, the positive electrode material 1 of the present invention can prevent structural defects in the coating layer 20 caused by excessive friction between particles, and ensure good charge and discharge performance of the positive electrode material 1. JPEG0007621415000001.jpg76164
[0027] FIG. 9A is an electrochemical impedance vector of the comparative example, the first embodiment, and the second embodiment of the present invention. FIG. 9B is an electrochemical impedance vector of the third and fourth embodiments of the present invention. FIG. 9A and FIG. 9B are measurements of the button batteries manufactured in the comparative example, the first embodiment, the second embodiment, the third embodiment, and the fourth embodiment of the present invention. As shown in FIG. 9A and FIG. 9B, the impedance of the first and second embodiments, in which the mixing time is 15 minutes, is not significantly different from that of the comparative example, whereas the impedance of the third and fourth embodiments, in which the mixing time is 30 minutes, is significantly increased compared to that of the comparative example. This shows that the positive electrode material 1 of the present invention can prevent structural defects in the coating layer 20 caused by excessive friction between particles by controlling the mixing time of the ternary material and the iron phosphate compound material, and can ensure the low impedance of the positive electrode material 1.
[0028] FIG. 10A is a charge curve diagram of the capacity retention rate vs. cycle number of the comparative example, the first embodiment of the present invention, and the second embodiment of the present invention. FIG. 10B is a discharge curve diagram of the capacity retention rate vs. cycle number of the comparative example, the first embodiment of the present invention, and the second embodiment of the present invention. FIG. 10A and FIG. 10B are measurements of the button batteries manufactured in the comparative example, the first embodiment of the present invention, and the second embodiment of the present invention at a 1C charge / discharge rate. As shown in FIG. 10A and FIG. 10B, there is no significant difference in cycle life between the embodiment of the present invention and the comparative example.
[0029] FIG. 11 is a capacity-cycle number discharge curve diagram of the comparative example, the first embodiment of the present invention, and the second embodiment of the present invention at different charge and discharge rates. FIG. 11 is a measurement of the button batteries manufactured in the comparative example, the first embodiment of the present invention, and the second embodiment of the present invention. The button batteries are charged and discharged for 3 cycles at charge and discharge rates of 0.1 C, 0.2 C, 0.5 C, and 1 C, then charged and discharged for 3 cycles at charge and discharge rates of 1 C charge / 3 C discharge, and 1 C charge / 5 C discharge, and finally charged and discharged for 3 cycles at a charge and discharge rate of 0.1 C. Table 2 shows the results at a discharge rate of 3 C. Table 3 shows the results at a discharge rate of 5 C. As shown in FIG. 11, there is no significant difference in the capacity performance between the first embodiment, the second embodiment, and the comparative example under the conditions of charge and discharge rates of 0.1 C, 0.2 C, 0.5 C, and 1 C. However, under the conditions of charge / discharge rates of 1 C charge / 3 C discharge and 1 C charge / 5 C discharge, the capacitance performance of the first and second examples is obviously superior to that of the comparative example. As shown in Table 2, at a discharge rate of 3 C, the capacitances of the first and second examples are increased by 86.2% and 134.8%, respectively, compared to the comparative example, that is, increased by about 1 time. As shown in Table 3, at a discharge rate of 5 C, the capacitances of the first and second examples are increased by 134.8% and 213.1%, respectively, compared to the comparative example, that is, increased by 1 to 2 times. This shows that the present invention can significantly improve the rate characteristics of the positive electrode material 1 by forming the coating layer 20 with an iron phosphate material having good rate characteristics. In addition, the weight ratio of the coating layer in the positive electrode material is, for example, 0.2 wt% to 5 wt%, which means that by simply adding a small amount of iron phosphate compound material, a coating layer 20 is formed that can improve the rate characteristics of the positive electrode material 1, and the manufacturing cost can be further reduced. JPEG0007621415000002.jpg52164JPEG0007621415000003.jpg52164
[0030] As described above, the present invention provides a high nickel cathode material with a coating layer and a method for manufacturing the same, which improve the high output density and rate characteristics while reducing costs. The cathode material includes a core layer and a coating layer that coats the core layer. The core layer is composed of a ternary material with a composition of Li[Ni x Co y Mn z O2, where x + y + z = 1, 0.8 < x < 1, 0 < y < 0.2, and 0 < z < 0.2. Due to the high nickel content in the core layer, a cathode material with high output density and low cost can be realized. The coating layer is composed of, for example, lithium iron phosphate (LiFePO4, LFP) material or heterosite iron phosphate (H-FP) material, and is formed by aggregation of a plurality of particles. Since the lithium iron phosphate material and the heterosite iron phosphate material themselves have good rate characteristics, the coating layer composed of these can further improve the rate characteristics of the cathode material. Also, the weight ratio of the coating layer in the cathode material is, for example, 0.2 wt% to 5 wt%. Since a coating layer that can improve the rate characteristics of the cathode material can be formed by adding only a small amount of iron phosphate compound material, the manufacturing cost can be further reduced. Each coating layer particle of the cathode material is coated with a carbon coating layer, which can enhance the electron conductivity between the coating layer particles and improve the performance of the cathode material. The ternary material with a high nickel content and the iron phosphate compound material are mixed, for example, by a mechanical mixing method, which is one of the mechanical fusion methods, to obtain a high nickel cathode material with a coating layer. The operating temperature during the mixing process is, for example, 25 °C to 45 °C, the time is 5 minutes to 25 minutes, and the range of the rotation speed is, for example, 1000 rpm to 3000 rpm. By controlling the mixing method, operating temperature, rotation speed, and time of the ternary material and the iron phosphate compound material, structural defects of the coating layer caused by high temperature and excessive friction between particles can be prevented, and it can be avoided that the electrolyte penetrates into the interior of the cathode material by forming a dense coating layer, ensuring low impedance and good charge-discharge performance of the cathode material.
[0031] The present invention can be modified or changed in various ways by those skilled in the art, but all such modifications and changes are included in the scope of the claims of the present invention without departing from the technical spirit of the present invention. [Explanation of symbols]
[0032] 1: Cathode material 10: Core layer 20: Covering layer 21: 1st particle 30: Carbon coating layer S1, S2: Step
Claims
1. A positive electrode material comprising a core layer and a coating layer, The core layer is made of a ternary material, and the composition of the ternary material is Li[Ni x Co y Mn z ]O 2 where x+y+z=1, 0.8<x<1, 0<y<0.2, and 0<z<0.2; The coating layer coats the core layer, the coating layer is made of an iron phosphate compound material, and the coating layer is formed by agglomerating a plurality of first particles, and the iron phosphate compound material is heterosite iron phosphate (Heterosite FePO 4 ).
2. 2. The positive electrode material according to claim 1, wherein the particle diameter of the core layer is 4 μm to 15 μm.
3. 2. The positive electrode material according to claim 1, wherein the first particles have a particle diameter of 0.1 μm to 3 μm.
4. The positive electrode material according to claim 1, further comprising a carbon coating layer that coats the first particles, the carbon coating layer having a thickness of 3 nm to 10 nm.
5. 2. The positive electrode material according to claim 1, wherein a weight ratio of the core layer in the positive electrode material is 95 wt % to 99.8 wt %.
6. 2. The positive electrode material according to claim 1, wherein the weight ratio of the coating layer to the positive electrode material is 0.2 wt % to 5 wt %.
7. 7. The positive electrode material according to claim 6, wherein the weight ratio of the coating layer to the positive electrode material is 0.2 wt % to 3 wt %.
8. A method for producing a positive electrode material, comprising the steps of: A ternary material is provided, the composition of the ternary material being Li[Ni x Co y Mn z ]O 2 and step (a) where x+y+z=1, 0.8<x<1, 0<y<0.2, and 0<z<0.2; providing an iron phosphate compound material; and mixing the ternary material and the iron phosphate compound material by a mechanical mixing method to obtain the positive electrode material, the positive electrode material having a core layer and a coating layer, the core layer being made of the ternary material, the coating layer coating the core layer, the coating layer being made of the iron phosphate compound material, the coating layer being formed by agglomeration of a plurality of first particles, the iron phosphate compound material being heterosite iron phosphate (Heterosite FePO 4 and (b) a step (c) of preparing a positive electrode material.
9. The method for producing a positive electrode material according to claim 8, wherein the particle diameter of the core layer is 4 μm to 15 μm.
10. The method for producing a positive electrode material according to claim 8, wherein the particle diameter of the first particles is 0.1 μm to 3 μm.
11. 9. The method for producing a positive electrode material according to claim 8, wherein the positive electrode material comprises a carbon coating layer that coats the first particles, and the carbon coating layer has a thickness of 3 nm to 10 nm.
12. 9. The method for producing a positive electrode material according to claim 8, wherein a weight ratio of the core layer in the positive electrode material is 95 wt % to 99.8 wt %.
13. 9. The method for producing a positive electrode material according to claim 8, wherein the weight ratio of the coating layer to the positive electrode material is 0.2 wt % to 5 wt %.
14. The method for producing a positive electrode material according to claim 13, wherein a weight ratio of the coating layer to the positive electrode material is 0.2 wt % to 3 wt %.
15. The method for producing a positive electrode material according to claim 8 , wherein the mechanical mixing method comprises a mechanical fusion method.
16. 9. The method for producing a positive electrode material according to claim 8, wherein the time for mixing the ternary material and the iron phosphate compound material by the mechanical mixing method is 5 minutes to 25 minutes.
17. 9. The method for producing a positive electrode material according to claim 8, wherein the rotation speed of the mechanical mixing method is in the range of 1000 rpm to 3000 rpm.
18. The method for producing a positive electrode material according to claim 8, wherein the operating temperature range of the mechanical mixing method is 25°C to 45°C.
Citation Information
Patent Citations
Positive electrode active material, nonaqueous electrolyte battery, and their manufacturing method
JP2002075368A
Positive electrode material for lithium ion secondary battery, positive electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2021157920A
Positive active material, positive electrode, lithium battery including the same, and method of manufacturing thereof
US20150228973A1